Occupational exposures and coronary heart disease in the Hamburg City Health Study (HCHS) – a cross-sectional study - Franziska Labe; Raphael Twerenbold; Betül Toprak; Peter Koch; Birgit-Christiane Zyriax; Sarah Affolderbach; Lukas Damerau; Hanno Hoven; Hajo Zeeb; Robert Herold; Volker Harth (BMC Public Health)
Abstract Background Coronary heart disease (CHD) is the leading cause of death among adults in Germany. There is evidence that occupational exposure to particulate matter, noise, psychosocial stressors, shift work and high physical workload are associated with CHD. The aim of this study is to identify occupations that are associated with CHD and to elaborate on occupational exposures associated with CHD by using the job exposure matrix (JEM) BAuA-JEM ETB 2018 in a German study population. Methods Cross-sectional data from 8,070 participants, members of the first sub-cohort of the Hamburg City Health Study (HCHS), was used. To classify occupations, we rely on standard occupational titles (ISCO-08). The level of exposure is assigned to each job using a JEM. CHD is measured by self-reported diagnosis. Absolute and relative frequencies were calculated. Using logistic regression, the association of CHD and standard occupation titles via ISCO-08 and the association of CHD and occupational exposures via JEM were calculated and adjusted for potentially confounding covariates. Multiple imputations with chained equations (MICEs) were applied for missing values. Sensitivity analyses were performed. Results The CHD prevalence in the study population was 4.6% (95% CI 4.2–5.1). Occupations associated with CHD were Physical and Engineering Science Technicians, Other Health Associate Professionals, General Office Clerks, Secretaries (general), Material Recording and Transport Clerks, Hairdressers, Beauticians and Related Workers, Electronics and Telecommunications Installers and Repairers, Other Craft and Related Workers, Car, Van and Motorcycle Drivers, Mobile Plant Operators and Domestic, Hotel and Office Cleaners and Helpers. Among occupational exposures retrieved from the JEM, Environmental Demands showed an association with CHD in the crude model but not after adjustment. The results remained robust in sensitivity analyses. Conclusions This study is the first to assess the association of a wide range of occupations and occupational exposures with CHD in a German study population. We found no association between occupational exposures and CHD after adjustment, but 11 occupations associated with CHD were identified. The results are limited by cross-sectional design, healthy worker effect (HWE), and small group sizes. Further studies with a larger sample and longitudinal design containing data on occupational history, occupational exposures and time of CHD diagnosis are needed.